(untitled) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2024)
This research aims to investigate the role of innovative leadership in shaping organizational culture and its impact on performance improvement in the Department of Housing and Settlement Areas of North Nias Regency. The research utilizes a qualitative method with a case study approach to gain a deep understanding of innovative leadership practices and organizational culture in that environment. Data were collected through interviews, observations, and document analysis. The analysis results indicate that innovative leadership plays a significant role in shaping an organizational culture that supports performance improvement. Innovative leadership is characterized by the ability to stimulate creativity and innovation among organizational members, support measured risk-taking, and facilitate the adaptation process to environmental changes. The organizational culture arising from innovative leadership tends to promote collaboration, continuous learning, and results-oriented orientation. The findings of this research provide insights into inhibiting and supporting factors in the implementation of innovative leadership and the formation of a performance-oriented organizational culture. The managerial implications of this research can guide organizational leaders in enhancing the effectiveness of innovative leadership and strengthening an organizational culture that supports the achievement of performance goals.